(untitled) (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The review is designed to draw up the specifics of diagnostic procedures in more convenient form for practitioners and researchers. Tick-borne diseases (TBDs) or otherwise called equine piroplasmosis (EP) are the foremost economic limitations to equids production. Thus, reducing the breeding capability and athletic performance of equids globally. Identification of these hemoparasites is crucial in understanding their distribution in the population and it is imperative to discern between species and subspecies that are responsible for the occurrence of the disease conditions. Materials and methods: Conventional procedures such as microscopic and serological evaluations do not usually meet these prerequisites. Diagnostic contrivances, for instance complement fixation test (CFT), indirect fluorescent antibody test (IFAT) and enzyme linked immunosorbent assay (ELISA) were efficaciously adapted for many years. Furthermore, DNA-based investigations for identification, diversification and classification of dissimilar hemoparasites were also established. Molecular investigative procedures, for example DNA hybridization, polymerase chain reaction (PCR), transcriptomics, proteomics, metagenomics and metabolomics, permit the uncovering of hemoparasites or tissues with optimal specificity, sensitivity and consistency. Results: Additionally, these procedures can be employed to detect definite species and subspecies. The prerequisite of these investigations must include proper premeditation and validation, these investigations provide an effective device for molecular studies, with greater benefits of flexibility to standard requirements. Application of these procedures for swotting TBDs or EP globally will be irreplaceable for a long period from now. Conclusion: The bourgeoning transcriptomics, proteomics, metagenomic and metabolomics could immensely add to the diagnosis of tick-borne diseases found in the tropical, subtropical and some temperate region of the world. http://dx.doi.org/10.5455/javar.2016.c148